Up and over. - Stone, Daniel (National geographic.)
Technically it's ancient technology. But now the two-millenia-old-principle of the Greek mathematician Archimedes has been deployed at gargantuan scale. The Three Gorges Dam, China's marvel on the Yangtze River, is one of the world's largest engineering projects -- the product of 37 million cubic yards of concrete. Its final feature, inaugurated in late 2016, is a new ship lift, a hydraulic seesaw that raises and lowers vessels as many as 371 feet to traverse the dam.